ESG performance and corporate carbon emission intensity: based on panel data analysis of A-share listed companies - Xie, Hanjin; Qin, Zilong; Li, Jun (Frontiers in Environmental Science, 2024)
This study investigates the impact of ESG performance on enterprise carbon emission intensity, using panel data from A-share listed companies over 2011-2022. The findings suggest that ESG can encourage enterprises to actively engage in environmental governance, enhancing their profitability and reducing carbon emission intensity, thereby achieving dual optimization of environmental and economic benefits. The mechanism test reveals the intermediary roles of institutional investors' participation, total factor productivity, and green technology innovation. Heterogeneity analysis indicates that the relationship between ESG performance and enterprise carbon emission intensity varies with different degrees of management shortsightedness, ownership separation, equity balance, legitimacy status, and industrial pollution characteristics, reflecting the heterogeneous influence driven by Intrinsic motivation and external factors. Notably, the mitigating influence of ESG on enterprise carbon emission intensity is mainly attributed to enhanced corporate profitability, which effectively decelerates the growth rate of enterprise carbon emissions, albeit insufficient to arrest the overall increase. This observation points to a certain degree of "green paradox" phenomenon. Overall, the analysis underscores the significant contribution of ESG in promoting enterprises' green transformation efforts.